New techniques of sinus trabeculectomy with prolonged hypotensive effect - E. A. Suleiman; S. Yu. Petrov (Российский офтальмологический журнал)
Long-term hypotensive effect in the postoperative period is one of the main tasks of modern glaucoma surgery.Purpose. To develop new modifications of sinus trabeculectomy in the surgical treatment of primary open-angle glaucoma (POAG), aimed at reducing scarring, normalization and prolongation of the outflow of intraocular fluid along newly formed pathways.Material and methods. During the first operation, a superficial scleral flap was formed. After trabeculectomy, the scleral flap was twisted by 180° in the middle, then fixed with sutures to the sclera. During the second operation, after the formation of the superficial scleral flap, and the trabeculectomy, the scleral flap was stitched in the middle and assembled in such a way that its width decreased by 1/3–1/2, after which it was fixed with sutures to the sclera. The operation was performed on 84 patients (84 eyes) aged 43 to 86 years (mean age 63.12 ± 1.17). Of these, 59 patients had POAG in advanced and far advanced stages, and 25 patients had a history of previous laser and surgical POAG interventions. The patients were divided into groups: 1a — 28 patients (28 eyes) who underwent sinus trabeculectomy with twisting the scleral flap, 1b — 29 patients (29 eyes) who underwent sinus trabeculectomy with stitching of the scleral flap and the control group – 27 patients (27 eyes) who underwent standard sinus trabeculectomy. The follow-up lasted 24 months. Standard methods (visometry, tonometry, computer perimetry, tonography, etc.) were used in the pre-surgical and post-surgical examination. In addition, we performed, in the early postoperative period, optical coherence tomography of the anterior eye segment followed by ultrasound biomicroscopy.Results. 1 month after surgery, the average IOP levels were simliar and remained low in all groups: 1a — 16.1 ± 0.5 mmHg, 1b — 16.4 ± 0.8 mmHg, 2 — 17.1 ± 0.7 mmHg. By the 1st year of the study, normalized IOP was maintained in both the two main groups and the control group. By 24 months of the follow-up, the effect was retained in 82.1 % in group 1a and in 82.7 % in group 1b. If the patients were IOP compensated with  medication, the effect rose to reach 92.8 % and 96.4 %. In the control group, the hypotensive success rate was 74 %, if patients IOP were compensated with medication it rose to 88.8 %.Conclusion. The developed new methods of sinus trabeculectomy for surgical treatment of glaucoma ensures a prolonged hypotensive effect.